Democratic Management and Citizen Participation of the Province of Tumbes-2023 - Pozada Limo, Ermi Kattia (2023)
This research aimed to determine the relationship between democratic management and citizen participation in the province of Tumbes, 2023. With an applied methodology, quantitative approach, propositional descriptive level, non-experimental design. With a population of 58 767 participants from the last elections in the province of Tumbes and a sample of 382 electoral participants from the last elections. Applying the survey and questionnaire with data collection instruments. The results were obtained 12.6% (48) state that the government never takes into account their needs and their cultural differences, minorities and social groups for the enactment of laws, 35.3% (135) almost never, regularly 31.9% (122), almost always 9.4% (36) and 10.7% (41) respond that the government always takes into account their needs and cultural differences, minorities and social groups for the enactment of laws. Concluding that democratic management has a direct and significant relationship with citizen participation, developing a proposal to improve democratic management.